TECTONIC ZONING OF THE SEDIMENTARY COVER IN THE DERYUGIN BASIN OF THE SEA OF OKHOTSK BASED ON STRUCTURAL-MATERIAL (LITHOPHYSICAL) INDICATORS - V. P. Semakin; A. V. Kochergin (Геодинамика и тектонофизика)
In terms of tectonics, the Deryugin basin (Fig. 1) is a part of the epi-Mesozoic Okhotsk plate comprising the heterogeneous basement that is mainly pre-Cenozoic (the lower structural stage) and the sedimentary cover that is mainly represented by the Paleogenic-Neogenic-Quaternary deposits with the Upper Cretaceous sedimentary rocks observed locally without a visible hiatus (the upper structural stage).The acoustic basement (AB) is composed of the metamorphosed Upper Cretaceous-Paleogenic silty-clayey-siliceous deposits (the western part of the region), amphibolites, gneisses, crystalline schists, weakly metamorphosed sandstones, siltstones, and mudstones (often siliceous), as well as intrusive and effusive rocks of basic, intermediate, and rarely persilic composition (the eastern part of the region). AB is generally dated as Mesozoic–Paleozoic.Results of tectonic zoning of the sedimentary cover based on material (lithophysical) indicators (Fig. 2) are represented in the format of maps showing lithophysical complexes (LC) within the limits of four regional seismo-stratigraphic complexes/structural layers (RSSC I-IV) corresponding to the following time intervals: the pre-Oligocene К2–P1-2 (RSSC I), the Oligocene – Lower Miocene P3–N11 (RSSC II), the Lower – Mid Miocene N11–2 (RSSC III), and the Upper Miocene – Pliocene N13–N2 (RSSC IV). Diverse lithological-facies associations composing the RSSCs are grouped into the following lithophysical complexes (LC): 1 - coal-bearing silty-clayey-sandy terrigenous, 2 - sandy-silty-clayey terrigenous, 3 - silty-clayey-siliceous, and 4 - sandy-silty-clayey volcanic [Sergeyev, 2006]. In the studied area (Fig. 2), the deposits of the pre-Oligocene RSSC are identified in limited areas within its northern, northwestern, and southwestern parts; they are represented by coal-bearing silty-clayey-sandy terrigenous and silty-clayey-siliceous LCs. Other RSSCs (II, III, and IV) in this area represented mostly by sandy-silty-clayey terrigenous and silty-clayey-siliceous LCs, and only the extreme southwestern part along the eastern Sakhalin coast contains narrow bands of the coal-bearing silty-clayey-sandy LC. The sandy-silty-clayey volcanic LC is absent in the Deryugin basin.Tectonic zoning of the sedimentary cover based on structural indicators is carried out with reference to the sediment-thickness map [Sergeyev, 2006] that was significantly revised in its segment showing the area of the Deryugin basin. Results of such zoning are represented in the format of a structural-tectonic map (Fig. 3) showing orientations and morphology of the structural elements of the sedimentary cover, the thickness of the sedimentary cover, and amplitudes of relative uplifts and troughs.With reference to the structural-tectonic map (see Fig. 3), the structural elements of different orders are grouped by their sizes, spatial positions and orientations and thus comprise structural zones (Fig. 4) that include relative uplifts and troughs that are considered as structural elements of smaller sizes (Fig. 5).Tectonic zoning of the sedimentary cover based on structural-material (lithophysical) indicators (Fig. 7–10) is carried out with reference to the maps of the lithophysical complexes of the four regional seismo-stratigraphic complexes/structural layers (see Fig. 2) and the map of high-order structural elements in the sedimentary cover (see Fig. 5).